Tree Growth Analysis as a Panacea for Sustainable Forest Management in Northeast Nigeria: Study of Lannea Kerstingii (Anacardiaceae) - Omijeh, Justus Eronmosele (Journal of Sustainability and Environmental Management, 2022)
Lannea kerstingii (Anacardiaceae) is found mainly in the Guinean and Sudanese savannas with health benefits and also used as timber, firewood and charcoal. Growth analysis of Lannea kerstingii was carried out to fill existing data gaps and enhance the practice of forestry for sustainable forest and environmental management. Twenty sample trees were assessed for different growth parameters yielding a coefficient of determination (r2) and Pearson’s correlation coefficient (r). The analysis showed the relationship between DBH and tree height, crown diameter, crown area, basal area, crown ratio and volume as 0.617, 0.264, 0.103, 0.907, 0.009, 0.864, 0.79, 0.051, 0.32, 0.95, 0.94, and 0.93 respectively. In addition to generating data for tree growth analysis, forestry extension and capacity should be deepened with provision of adequate funding to relevant agencies to promote biodiversity conservation.